Thiamine Is Required for Virulence and Survival of Pseudomonas syringae pv. tomato DC3000 on Tomatoes - Liu, Jun; Zhang, Xuejiang; Deng, Siyi; Wang, Hua; Zhao, Youfu (Frontiers in Microbiology, 2022)
Pseudomonas syringae pv. tomato strain DC3000 (PstDC3000) is an important plant pathogen that infects tomato and Arabidopsis. Thiamine and its derivative thiamine pyrophosphate (TPP) are cofactors that play an important role in the growth and survival of many bacterial microorganisms. However, the role of thiamine-related genes has not been determined in PstDC3000. Hence, to investigate the role of TPP in growth, resistance to stresses and virulence of PstDC3000, double and quadruple mutants of thiamine biosynthesis-related genes (thiD/E, thiS/G and thiD/E/S/G deletion mutants) as well as a single mutant of a lipoprotein-related gene (apbE) were constructed. Our results showed that growth of the thiD/E, thiS/G and thiD/E/S/G mutants in mannitol-glutamate (MG) medium were significantly lower than that of the wild type (WT), and their growth could be restored to the WT level with addition of exogenous thiamine; whereas mutation of the apbE gene did not affect its growth in vitro. While tolerance to acid, osmotic and oxidative stresses for the double mutants was similar to the WT, tolerance to stresses for the apbE mutant was reduced as compared to the WT. In addition, all four mutants exhibited reduced virulence and growth on tomato. However, when the double and quadruple mutants inoculated with exogenous thiamine, virulence and growth rate of these mutants restored to the WT level. These results indicated that the thiD/E, thiS/G, and thiD/E/S/G mutants exhibiting growth deficiency in planta are probably due to lack of thiamine biosynthesis, thus reducing colonization in tomato. On the other hand, it is possible that the apbE mutant exhibited reduced stress tolerances, thus resulting in reduced colonization. Overall, our findings suggest that the thiamine biosynthetic (TBS) pathway plays an important role in colonization and infection of PstDC3000. Therefore, thiamine biosynthetic pathway could be used as targets to develop new control measures for bacterial spot of tomato.